The effect of supply chain resilient strategies on operational performance of humanitarian organisations in Zimbabwe during the Coronavirus period - Dumisani Mawonde; Bindu Samuel; Josphat Nyoni; Allan C. Muzenda (Cogent Business & Management, 2023)
The outbreak of the Coronavirus pandemic disrupted global supply chains, creating acute shortages of goods and services to support the operations of many organisations. In Zimbabwe, this situation affected the operations of humanitarian organisations since the pandemic disrupted the supplies of procurement requirements on time for the purposes of humanitarian aid. This study therefore examined the effects of supply chain resilience strategies on operational performance of humanitarian organisations in Zimbabwe during the Coronavirus period. A pragmatic research philosophy and a descriptive survey research design were employed. A sample of 28 supply chain management professionals was randomly selected from a targeted population of 30 in humanitarian organisations in Harare and only 25 responded, whereas interviews were conducted with five supply chain management professionals. Quantitative data was scrutinised by means of SPSS and AMOS programs (versions 22.0), while qualitative data from interviews was analysed using thematic scrutiny. Structural Equation Modelling (SEM) was used to determine the results, and the convergent validity of the measurement model was tested. The study findings show that supply chain resilience strategies had a significant positive effect on operational performance in humanitarian organisations during the Coronavirus period. The study concluded that in Zimbabwe, humanitarian organisations are familiar with supply chain resilience strategies and that supply chain resilient strategies that were analysed have a positive and significant effect on stock availability, delivery flexibility, and delivery time. The study recommends humanitarian organisations to be agile in supply chains, to embrace cross-sector collaborations, and to plan and prepare for unforeseeable supply chain disruptions as this improves their operational performance during the pandemics.
Keywords: 650; Coronavirus; operational performance; supply chain disruption; supply chain resilience